Statistical perspective and pollution indicator in Mengkabong Mangrove Sediment Sabah - Radojevic, Miroslav; Praveena, Sarva Mangala; Abdullah, Mohd Harun (Canadian Center of Science and Education, 2008)
The role of tidal processes on intertidal surface sedimentsis frequently stated but rarely investigated due to the methodological restrictions. This study provides a basis for describing the tidal effects on the mangrove sediment. It reports investigations into the chemical composition of mangrove surface sediment in Mengkabong lagoon, Sabah, Malaysia. The levels of 16 parameters were determined in 33 surface sediment samples at high and low tides. The studied parameters showed high values at high tide compared to low tide. The tidal process showed there is a high contribution of seawater that brings additional ions such as Na, Mg and K into the mangrove system at high tide whereas at low tide, lower contribution of seawater was observed. Spearman correlation coefficient was used for the statistical characterizations of mangrove surface sediment at high and low tides. Relationships between physicochemical parameters, metals, granulometric fractions, organic matter and base cations at high and low tides were observed. Geoaccumulation Index calculations showed current sediment quality of Mengkabong mangrove sediments could be classified as having background concentrations of Al, Cu, Fe, and Zn, and as unpolluted with regard to Pb. These findings are important for future research which will explain the chemistry that lies in mangrove sediment.